Genome Fractionation and Loss of Heterozygosity in Hybrids and Polyploids: Mechanisms, Consequences for Selection, and Link to Gene Function - Janko, Karel; Bartoš, Oldřich; Kočí, Jan; Roslein, Jan; Drdová, Edita Janková; Kotusz, Jan; Eisner, Jan; Mokrejš, Martin; Štefková-Kašparová, Eva (Molecular biology and evolution, 2021)
Hybridization and genome duplication have played crucial roles in the evolution of many animal and plant taxa. The subgenomes of parental species undergo considerable changes in hybrids and polyploids, which often selectively eliminate segments of one subgenome. However, the mechanisms underlying these changes are not well understood, particularly when the hybridization is linked with asexual reproduction that opens up unexpected evolutionary pathways. To elucidate this problem, we compared published cytogenetic and RNAseq data with exome sequences of asexual diploid and polyploid hybrids between three fish species; Cobitis elongatoides, C. taenia, and C. tanaitica. Clonal genomes remained generally static at chromosome-scale levels but their heterozygosity gradually deteriorated at the level of individual genes owing to allelic deletions and conversions. Interestingly, the impact of both processes varies among animals and genomic regions depending on ploidy level and the properties of affected genes. Namely, polyploids were more tolerant to deletions than diploid asexuals where conversions prevailed, and genomic restructuring events accumulated preferentially in genes characterized by high transcription levels and GC-content, strong purifying selection and specific functions like interacting with intracellular membranes. Although hybrids were phenotypically more similar to C. taenia, we found that they preferentially retained C. elongatoides alleles. This demonstrates that favored subgenome is not necessarily the transcriptionally dominant one. This study demonstrated that subgenomes in asexual hybrids and polyploids evolve under a complex interplay of selection and several molecular mechanisms whose efficiency depends on the organism's ploidy level, as well as functional properties and parental ancestry of the genomic region.
Keywords: Loss of Heterozygosity; hemizygous deletions; polyploidy; Genome, Plant; genom rostlinný; ztráta heterozygozity; molekulární evoluce; Evolution, Molecular; Cypriniformes; gene conversions; hybridization; Animals; zvířata; asexual reproduction; Hybridization, Genetic; Diploidy; máloostní; hybridizace genetická; Polyploidy; diploidie; loss of heterozygosity; polyploidie